Hypoxia-induced PD-L1/PD-1 crosstalk impairs T-cell function in sleep apnoea. Issue 4 (19th October 2017) - Cubillos-Zapata, Carolina; Avendaño-Ortiz, Jose; Hernandez-Jimenez, Enrique; Toledano, Victor; Casas-Martin, Jose; Varela-Serrano, Anibal; Torres, Marta; Almendros, Isaac; Casitas, Raquel; Fernández-Navarro, Isabel; Garcia-Sanchez, Aldara; Aguirre, Luis A.; et al.
Obstructive sleep apnoea (OSA) is associated with higher cancer incidence, tumour aggressiveness and cancer mortality, as well as greater severity of infections, which have been attributed to an immune deregulation. We studied the expression of programmed cell death (PD)-1 receptor and its ligand (PD-L1) on immune cells from patients with OSA, and its consequences on immune-suppressing activity. We report that PD-L1 was overexpressed on monocytes and PD-1 was overexpressed on CD8 + T-cells in a severity-dependent manner. PD-L1 and PD-1 overexpression were induced in both the human in vitro and murine models of intermittent hypoxia, as well as by hypoxia-inducible factor-1α transfection. PD-L1/PD-1 crosstalk suppressed T-cell proliferation and activation of autologous T-lymphocytes and impaired the cytotoxic activity of CD8 + T-cells. In addition, monocytes from patients with OSA exhibited high levels of retinoic acid related orphan receptor, which might explain the differentiation of myeloid-derived suppressor cells. Intermittent hypoxia upregulated the PD-L1/PD-1 crosstalk in patients with OSA, resulting in a reduction in CD8 + T-cell activation and cytotoxicity, providing biological plausibility to the increased incidence and aggressiveness of cancer and the higher risk of infections described in these patients. PD-L1/PD-1 crosstalk is upregulated in obstructive sleep apnoea patients and immunomodulates T-cell response http://ow.ly/gBEx30dZ7dd